Analysis of Dentists’ Perceptions Regarding Selection of the Metallic Dental Implant Material - Hiba Pervaiz, Sehreen Moorat, Natasha Mukhtiar, Umer Khayyam, Faryal Manzoor, Jawaid Sultan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the perceptions of the dentist regarding most appropriate metallic biomaterials and selected materials based on their biocompatibility and mechanical stability. Material and methods: This descriptive study of dental implants was conducted at the LUMHS Dental department, ISRA Dental department, ADCC Hyderabad, Bhittai dental hospital Mirpur-khas. The study duration was six months. All the dentists having minimum experience of one year, both genders and of either age, were included. Data has been collected by the gathering and measuring information on target variables through a questionnaire and interviews with the dentists. All collecting all the information the data was analyzed using SPSS version 26. Results: A total of 80 dentists from different health departments were interviewed to evaluate their perceptions of the dentist regarding most appropriate metallic biomaterials and selected materials based on their biocompatibility and mechanical stability. Out of all females were 63.7% and remaining were males. Most of the dentists agreed with the painful dental implant procedure depending on the anesthesia choices. All the patients can remove metallic dental implants from the mouth. Gold (Au) alloys for dental implants because it is cost effective. Majority of the study subjects replied that the Cobalt-chromium alloy metallic implants cause trauma/injury to the teeth and have a higher chance of corrosion. The best synonymies the word reliable for metallic dental implant in their opinion, which is the mouth - friendly, light weighted and cost effective. The most reliable/suitable and most biocompatible metal to use as a dental implant is Titanium. According to dentists, the metals supremely carry the drying agent for a longer period are Titanium and Zirconium and they were thought that the dental implants can last a lifetime if they are taken care of properly. Conclusion: As per study conclusion the Titanium is the most reliable/suitable and biocompatible metal to use as a dental implant, according to the study’s findings, and Titanium and Zirconium are the metals that best carry the drying agent for a longer time, according to dentists. Because gold (Au) alloys are more cost effective, and Cobalt-chromium alloys metallic implants create more complications. If people take excellent care of your dental implants, they can last a lifetime.